Genotype–phenotype correlation of congenital anomalies in multiple congenital anomalies hypotonia seizures syndrome (MCAHS1)/PIGN‐related epilepsy. Issue 1 (23rd September 2015) - Fleming, Leah; Lemmon, Monica; Beck, Natalie; Johnson, Maria; Mu, Weiyi; Murdock, David; Bodurtha, Joann; Hoover‐Fong, Julie; Cohn, Ronald; Bosemani, Thangamadhan; Barañano, Kristin; Hamosh, Ada
Abstract : Mutations in PIGN, resulting in multiple congenital anomalies‐hypotonia‐seizures syndrome, a glycosylphosphatidylinositol anchor deficiency, have been published in four families to date. We report four patients from three unrelated families with epilepsy and hypotonia in whom whole exome sequencing yielded compound heterozygous variants in PIGN . As with previous reports Patients 1 and 2 (full siblings) have severe global developmental delay, gastroesophageal reflux disease, and minor dysmorphic features, including high palate, bitemporal narrowing, depressed nasal bridge, and micrognathia; Patient 3 had early global developmental delay with later progressive spastic quadriparesis, intellectual disability, and intractable generalized epilepsy; Patient 4 had bilateral narrowing as well but differed by the presence of hypertelorism, markedly narrow palpebral fissures, and long philtrum, had small distal phalanges of fingers 2, 3, and 4, absent distal phalanx of finger 5 and similar toe anomalies, underdeveloped nails, unusual brain anomalies, and a more severe early clinical course. These patients expand the known clinical spectrum of the disease. The severity of the presentations in conjunction with the patients' mutations suggest a genotype–phenotype correlation in which congenital anomalies are only seen in patients with biallelic loss‐of‐function. In addition, PIGN mutations appear to be panethnic and may be an underappreciated cause of epilepsy. © 2015 Wiley Periodicals, Inc.